Long-term efficacy of remission-maintenance regimens for ANCA-associated vasculitides. Issue 8 (3rd May 2018) - Terrier, Benjamin; Pagnoux, Christian; Perrodeau, Élodie; Karras, Adexandre; Khouatra, Chahera; Aumaître, Olivier; Cohen, Pascal; Decaux, Olivier; Desmurs-Clavel, Hélène; Maurier, François; Gobert, Pierre; Quémeneur, Thomas; et al.
Abstract : Objective: To compare long-term efficacy of remission-maintenance regimens in patients with newly diagnosed or relapsing antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitides. Methods: The 28-month Maintenance of Remission using Rituximab in Systemic ANCA-associated Vasculitis trial compared rituximab with azathioprine to maintain remission in patients with newly diagnosed or relapsing granulomatosis with polyangiitis, microscopic polyangiitis or renal-limited ANCA-associated vasculitis. Thereafter, prospective patient follow-up lasted until month 60. The primary endpoint was the major-relapse rate at month 60. Relapse and serious adverse event-free survival were also assessed. Results: Among the 115 enrolled patients, only one was lost to follow-up at month 60. For the azathioprine and rituximab groups, respectively, at month 60, the major relapse-free survival rates were 49.4% (95% CI 38.0% to 64.3%) and 71.9% (95% CI 61.2% to 84.6%) (p=0.003); minor and major relapse-free survival rates were 37.2% (95% CI 26.5% to 52.2%) and 57.9% (95% CI 46.4% to 72.2%) (p=0.012); overall survival rates were 93.0% (95% CI 86.7% to 99.9%) and 100% (p=0.045) and cumulative glucocorticoid use was comparable. Quality-adjusted time without symptoms and toxicity analysis showed that rituximab-treated patients had 12.6 months more without relapse or toxicity than those given azathioprine (p<0.001). Antiproteinase-3-ANCA positivity and azathioprine arm were independently associated with higher risk of relapse. HRs of positive ANCA to predict relapse increased over time. Conclusion: The rate of sustained remission for ANCA-associated vasculitis patients, following rituximab-based or azathioprine-based maintenance regimens, remained superior over 60 months with rituximab, with better overall survival. Trial registration number: NCT00748644 .